Bob the Builder. Built to be wild - Cockle, Jackie; Osmond, Donny; Quatro, Suzi.; HOT Animation (Firm) ([Allen, Tex.] : Hit Entertainment, 2006)
Bob and his friends head out to the wild west hot on the trail of a secret treasure. They get a little help in their endeavors from a friendly cowgirl named Rio, and her horse, Jackaroo.
Full screen (1.33:1) presentation; Dolby Digital.
Title from container.
Voices: Donny Osmond and Suzi Quatro.
DVD.
English, dubbed French or dubbed Spanish dialogue; closed- captioned.
Keywords: Bob the Builder (Fictitious character) -- Juvenile drama; Construction workers -- Juvenile drama; Construction equipment -- Juvenile drama; Television programs for children; Television programs for the hearing impaired; Animated television programs